Service Quality And Availability To Improve Client Satisfaction - Saskia Nurul Amalia; Richa Puspita Nur Musthaqfiroh; Farah Ayuningtyas (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The Effect of Service Quality and Facilities on Customer Satisfaction at AHASS Bintang Motor Jaya Plered Customers" is the subject of this study's analysis and determination. Customers of AHASS Bintang Motor Jaya Plered made up the study's population. Purposive sampling was employed to gather samples from up to 100 respondents, and multiple regression analysis was performed. Validity tests, reliability tests, multiple linear regression analyses, classical assumption tests, partial hypothesis testing with t tests, and simultaneous testing with f tests are the analysis techniques that are employed. The facility variable also had a positive and significant effect on customer satisfaction with a value of (2.519 ≥ 1.660) and a significant value of (0.000 <0.05), according to the results of the t test, which also showed that the service quality variable had a positive and significant effect on customer satisfaction with tcount> ttable (7,106 ≥ 1.660). The F test, which is derived from the results of the Fcount of 66,278> Ftable of 3.09 and a significant value of 0.000 <0.05, reveals the simultaneous testing between service quality and facilities on customer satisfaction. This indicates that the quality of services and facilities has a positive and significant effect on customer satisfaction of AHASS Bintang Motor Jaya Plered customers.